Responses of the Endophytic Bacterial Communities of Juncus acutus to Pollution With Metals, Emerging Organic Pollutants and to Bioaugmentation With Indigenous Strains - Syranidou, Evdokia; Thijs, Sofie; Avramidou, Marina; Weyens, Nele; Venieri, Danae; Pintelon, Isabel; Vangronsveld, Jaco; Kalogerakis, Nicolas (Frontiers in Plant Science, 2018)
Plants and their associated bacteria play a crucial role in constructed wetlands. In this study, the impact of different levels of pollution and bioaugmentation with indigenous strains individually or in consortia was investigated on the composition of the endophytic microbial communities of Juncus acutus. Five treatments were examined and compared with increasing levels of metal pollution (Zn, Ni, Cd) and emerging pollutants (BPA, SMX, CIP), enriched with different combinations of single or mixed endophytic strains. The responses of the communities of roots and shoots were different, depending on the inoculant and the levels of metals and organic pollutants. The differences in remediation effectiveness and the effects of bioaugmentation were remarkable. Inoculation of the separate strains as well as the consortium significantly enhanced Zn concentrations while it also increased Ni concentrations in the tissues of J. acutus. This study highlights the effects of pollution and inoculation on phytoremediation efficiency based on a better understanding of the plant microbiome community composition. Our results indicate that inoculation with selected indigenous endophytes is a promising approach to improve the efficiency wastewater remediation.